Adjuvant system AS02V enhances humoral and cellular immune responses to pneumococcal protein PhtD vaccine in healthy young and older adults: Randomised, controlled trials. Issue 4 (15th January 2015) - Leroux-Roels, Isabel; Devaster, Jeanne-Marie; Leroux-Roels, Geert; Verlant, Vincent; Henckaerts, Isabelle; Moris, Philippe; Hermand, Philippe; Van Belle, Pascale; Poolman, Jan T.; Vandepapelière, Pierre; Horsmans, Yves
Highlights Pneumococcal protein vaccines potentially provide serotype-independent protection. A PhtD vaccine with or without adjuvant was assessed in healthy young/older adults. All formulations had an acceptable reactogenicity profile, without safety concerns. PhtD/AS02V induced PhtD-specific antibody, CD4 T cell and memory B cell responses. Immune responses in older adults were partly restored with AS02V adjuvant system.